A measure of core wage inflation - Martin Almuzara; Richard Audoly; Davide Melcangi (Federal Reserve Bank of New York, 2024)
We recover the persistent ("core") component of nominal wage growth over the past twenty-five years in the United States. Our approach combines worker-level data with time-series smoothing methods and can disentangle the common persistence of wage inflation from the persistence specific to some subgroup of workers, such as workers in a specific industry. We find that most of the business cycle fluctuations in wage inflation are persistent and driven by a common factor. This common persistent factor is particularly important during inflationary periods, and it explains 80 to 90 percent of the post-pandemic surge in wage inflation. Contrary to standard measures of wage inflation, the persistent component of wage inflation contemporaneously co-moves with labor market tightness.
Keywords: C33; E24; 330; wage inflation; persistence; factor models